Application of MALDI-TOF MS for identification of environmental bacteria: A review. (1st March 2022) - Ashfaq, Mohammad Y.; Da'na, Dana A.; Al-Ghouti, Mohammad A.
Abstract: Bacteria play a variety of roles in the environment. They maintain the balance in the ecosystem and provide different ecosystem services such as in biogeochemical cycling of nutrients, biodegradation of toxic pollutants, and others. Therefore, isolation and identification of different environmental bacteria are important to most environmental research. Due to the high cost and time associated with the conventional molecular techniques, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has gained considerable attention for routine identification of bacteria. This review aims to provide an overview of the application of MALDI-TOF MS in various environmental studies through bibliometric analysis and literature review. The bibliometric analysis helped to understand the time-variable application of MALDI-TOF MS in various environmental studies. The categorical literature review covers various environmental studies comprising areas like ecology, food microbiology, environmental biotechnology, agriculture, and plant sciences, which show the application of the technique for identification and characterization of pollutant-degrading, plant-associated, disease-causing, soil-beneficial, and other environmental bacteria. Further research should focus on bridging the gap between the phylogenetic identity of bacteria and their specific environmental functions or metabolic traits that can help in rapid advancements in environmental research, thereby, improving time and cost savings. Highlights: It provides an overview of MALDI-TOF MS applications in environmental studies. Isolation and identification of environmental bacteria are important to environmental research. MALDI-TOF MS has high accuracy and precision for the identification of various types of bacteria. It is used for rapid identification of bacteria present in water, air, and different surfaces.